Low Handgrip strength and its lifestyle and physiological correlates among Taiwanese University Students: A cross-sectional study - Shao-Yun Chien; Yu-Kuei Teng; Hsiao-Wen Hung; Tsuei-Hung Wang; Mei-Chen Ho; Ya-Ling Tzeng (PLoS ONE, 2026)
Handgrip strength is a well-established indicator of muscular fitness and an early predictor of adverse long-term health outcomes. However, limited research has examined HGS and its determinants among young adults in East Asia. This cross-sectional study investigated the association between lifestyle and physiological factors and low HGS in 501 Taiwanese university students aged 18–25 (168 men, 333 women). Participants completed questionnaires on physical activity, sedentary time, and dietary behavior, and underwent anthropometric measurements including body mass index (BMI), mid-upper arm circumference, and handgrip strength. Low handgrip strength was defined using the sex-specific criteria established by the Asian Sarcopenia Working Group in 2019 (men < 28 kg; women <18 kg). Results showed that 6.2% of participants had low handgrip strength (8.3% in men, 5.1% in women). Men had significantly higher average handgrip strength than women (38.0 ± 7.8 kg vs. 24.6 ± 4.4 kg, p < .001). Upper arm circumference and handgrip strength showed the strongest correlation in both sexes ( p < .001). Logistic regression analysis revealed that smaller upper arm circumference (OR = 0.80, p = .003 per 1 cm increase), insufficient moderate-to-vigorous physical activity (OR = 0.40, p = .055), and male sex (OR = 5.28, p = .001) were significantly associated with poor handgrip strength. Dietary habits and sedentary time were not significantly associated with handgrip strength. These findings highlight the importance of early identification of muscle weakness and promoting physical fitness training in young adults. Men with smaller arm circumference and lower activity levels showed a significant association with low HGS and may benefit from early monitoring and targeted intervention. Incorporating muscle strength assessment and activity promotion into early adulthood health programs may help preserve muscular fitness, prevent future sarcopenia, and support healthier aging trajectories in East Asian populations.